Efeito de variáveis físico-quimicas na acidez de nopalea cochenillifera cv. Ipa sertânia (cactacea) no semiárido potiguar - Morais, Akelina Márcia Bezerra de (Universidade Federal Rural do Semi-Árido, 2020)
The present work aims to verify the variations in acidity of the IPA Sertânia forage palm in the semi-arid region of Rio Grande do Sul. The specific objectives are: to measure the hydrogenionic potential (pH) of the forage palm IPA Sertânia, in order to observe the acidity, mainly comparing the daytime with the night, typical of the metabolism of these plants; measure the pH of the IPA Sertânia forage palm at 6-hour intervals during the day, in order to observe, compare and analyze acidity at different times. This is an experimental, descriptive research with a qualitative approach, based on the observation of pH in five experiments with four samples identified by blocks: I, II, III and IV. The pH records were made at three intervals of six hours, counting from 06:00 to 12:00, from 12:00 to 18:00 and from 18:00 to 00:00. It was verified that the average pH levels go through variations in two ranges of intervals: from 06:00 to 12:00, in which, in the first hour, the acidity levels of the IPA Sertânia Forrageira Palma are higher, reaching 3, 62, while in the second hour, the acidity levels tend to be much lower, represented by the pH value of 4.93. In the second interval, which is from 12:00 to 00: 00h, the acidity levels are less high in the first hour, in the second the acidity increases and reaches 3.75, probably with the temperature drop, a characteristic phenomenon of the semiarid region. It is concluded that, the results confirm the hypothesis that, although acidity is a characteristic of Nopalea cochenillifera, it undergoes variations, especially when comparing nighttime and daytime pH. This finding raises questions about factors that can interfere in this variation, being necessary to study them, in order to know the ways of handling the plant.
Monografia
Keywords: Acidez; Semiárido; Cactáceas; Acidity; Semiarid; Cacti; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL